구어 전사 말뭉치의 언어학적 주석과 활용 - 안의정(Ahn, Eui-Jeong) (동서인문학, 2020)
본 논문의 목적은 구어 전사 말뭉치의 주석에 대한 전반적인 이해를 돕고, 보다 효율적인 주석 방법에 대해 알아보며, 유형별 주석의 활용 방안에 대해 정리하기 위한 것이다. 그리고 한국어 구어 말뭉치의 구축 방법론과 현황을 파악하기 위하여 형태 주석과 구문 주석, 담화 주석에 대해 개괄적으로 살펴보는 것을 목적으로 하였다. 먼저 말뭉치 주석에 대한 기본적인 논의를 시작으로, 구어 전사 말뭉치 주석의 형식과 구축 단계에 대해 살펴보았다. 언어학적 주석 중에서 가장 기본이라고 할 수 있는 형태 주석과 그 외에 구문 주석, 담화 주석의 구축 사례에 대해서도 살펴보았다. 가장 많은 말뭉치가 구축되고 연구된 형태 주석에 대해서는 음운의 축약을 이용한 연구 사례에 대해서도 살펴보았다. 한국어 구어의 구문 분석을 위해서는 의존문법을 사용하는 것이 더 바람직한데, 그 이유는 구 구조문법은 서로 인접해 있는 성분들의 관계를 확정하고 다시 다른 인접해 있는 성분들의 관계를 정하는 방식이기 때문에 구어처럼 어순이 자유로운 경우는 취하기 어렵기 때문이다. 담화 주석은 SWBD-DAMSL 체계를 한국어에 적용한 사례를 알아보았는데, 아직까지는 일상적인 자연언어 대화에서는 이루어진 바가 없고, 인위적인 대화에서 이루어졌다. The purpose of this paper is to help the overall understanding of spoken transcription corpus annotations, to learn more efficient annotation methods, and to organize the usage of annotations by type. The purpose of this study was to provide a general overview of POS taggings, syntax annotations, and discourse annotations in order to grasp the methodology and current status of Korean spoken language corpus. Beginning with a basic discussion of corpus annotations, I looked at the format and construction stages of spoken transcription corpus annotations. I looked at the POS tagging, which is the most basic of linguistic annotations, and the construction examples of syntax annotations and discourse annotations. For the POS taggings with the most corpus constructed and studied, I also reviewed the case studies using the contractions. For syntax parsing of Korean spoken language, it is more preferable to use dependent syntax, because phrase structure rule is a way of determining the relationship between adjacent components and again the relationship between other adjacent components. This is not suitable because spoken language is free. In the discourse annotation, I examined the application of the SWBD-DAMSL system to Korean language, which has not been done in ordinary natural language conversations yet, but in artificial conversations. KCI Citation Count: 0